IMPLEMENTATION OF OPEN SELECTION POLICY FOR HIGH LEADERSHIP POSITIONS ON THE EFFECTIVENESS OF HUMAN RESOURCES IN KLATEN REGENCY GOVERNMENT - Mulyani, Sri; Istiatin, Istiatin; Sudarwati, Sudarwati (STIE Pelita Nusantara Semarang, 2023)
This study collects data through observation, documentation, interviews, questionnaires, and case studies to examine the effects of leadership, communication skills, competence, and motivation. There were 1,084 workers surveyed from across 13 different offices and departments in the Klaten district. Purposive sampling is a technique used by academics. A total of 130 employees from various government offices in the Klaten regency will serve as the study's sample population (8 percent of the total population). Researchers will select 10 respondents from each office, agency, and department in the region. In this study, we used SPSS version 24 to conduct a multiple regression analysis. Research and analysis yielded variables measuring professionalism, integrity, productivity, and expertise in all areas of the Klaten provincial government's organizational structure for effective management. value of adjusted R square (R2) equal to 0.644%. Determination or contribution of variables such as professionalism, integrity, competence, and performance on the job to organizational effectiveness in the Klaten regency's administrative arm, the Organisasi Perangkat Daerah (OPD). The total increase in other variables, such as work ethic, workplace discipline, education, and so on, is just 35.6%.